Assessing the similarity of ligand binding conformations with the Contact Mode Score. (October 2016) - Ding, Yun; Fang, Ye; Moreno, Juana; Ramanujam, J.; Jarrell, Mark; Brylinski, Michal
Graphical abstract: Highlights: A novel method to measure the similarity of ligand binding conformations is proposed. The Contact Mode Score (CMS) is less dependent on the ligand size than the RMSD. The analysis of ligand binding conformations includes the protein environment. The extended CMS (XCMS) can be used to compare non-identical protein-ligand complexes. Abstract: Structural and computational biologists often need to measure the similarity of ligand binding conformations. The commonly used root-mean-square deviation (RMSD) is not only ligand-size dependent, but also may fail to capture biologically meaningful binding features. To address these issues, we developed the Contact Mode Score (CMS), a new metric to assess the conformational similarity based on intermolecular protein-ligand contacts. The CMS is less dependent on the ligand size and has the ability to include flexible receptors. In order to effectively compare binding poses of non-identical ligands bound to different proteins, we further developed the eXtended Contact Mode Score (XCMS). We believe that CMS and XCMS provide a meaningful assessment of the similarity of ligand binding conformations. CMS and XCMS are freely available athttp://brylinski.cct.lsu.edu/content/contact-mode-score andhttp://geaux-computational-bio.github.io/contact-mode-score/ .